1994
DOI: 10.1083/jcb.125.2.437
|View full text |Cite
|
Sign up to set email alerts
|

Ep-CAM: a human epithelial antigen is a homophilic cell-cell adhesion molecule.

Abstract: Abstract. The epithelial glycoprotein 40 (EGP40, also known as GA733-2, ESA, KSA, and the 17-1A antigen), encoded by the GA-733-2 gene, is expressed on the baso-lateral cell surface in most human simple epithelia. The protein is also expressed in the vast majority of carcinomas and has attracted attention as a tumor marker. The function of the protein is unknown. We demonstrate here that EGP40 is an epithelium-specific intercellular adhesion molecule. The molecule mediates, in a Ca2+-independent manner, a homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
367
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(379 citation statements)
references
References 23 publications
10
367
1
1
Order By: Relevance
“…Transfection with D5.7A cDNA increased the adhesive capacity of cells, even if the binding partner did not express D5.7A, which points towards heterophilic binding. The heterophilic nature of the D5.7A binding is in discordance with reports by other groups on homophilic binding of human Ep-CAM (=EGP314, GA733-2) Litvinov et al, 1994). Litvinov et al (1994) describe homophilic, Ca 2+ -independent adhesion of murine cell lines transfected with the human EGP40 cDNA, the adhesive interaction being of the strength to allow sorting of EGP-transfected from parental nontransfected lines.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Transfection with D5.7A cDNA increased the adhesive capacity of cells, even if the binding partner did not express D5.7A, which points towards heterophilic binding. The heterophilic nature of the D5.7A binding is in discordance with reports by other groups on homophilic binding of human Ep-CAM (=EGP314, GA733-2) Litvinov et al, 1994). Litvinov et al (1994) describe homophilic, Ca 2+ -independent adhesion of murine cell lines transfected with the human EGP40 cDNA, the adhesive interaction being of the strength to allow sorting of EGP-transfected from parental nontransfected lines.…”
Section: Discussionmentioning
confidence: 49%
“…The heterophilic nature of the D5.7A binding is in discordance with reports by other groups on homophilic binding of human Ep-CAM (=EGP314, GA733-2) Litvinov et al, 1994). Litvinov et al (1994) describe homophilic, Ca 2+ -independent adhesion of murine cell lines transfected with the human EGP40 cDNA, the adhesive interaction being of the strength to allow sorting of EGP-transfected from parental nontransfected lines. Instead, Fornaro et al (1995) found no evidence for homophilic binding of Trop-2 + (GA733-1) or Trop-1 + (GA733-2) cells.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The Epithelial cell adhesion molecule (Ep-CAM) is a transmembrane glycoprotein expressed on most human epithelial cells, functioning as a homophilic cell-cell adhesion molecule [1]. Ep-CAM is a potential target for antibody based therapies [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%